Culture and sentimental journey in the poetry by Manuel Vázquez Montalbán - Luengo Gascón, Elvira (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
In 2008, Complete Poetry (1963-2003) Memory and Desire by Manuel Vázquez Montalbán was published and it brings together the Catalan author's poetic work. His poetic work is less well known than his narrative work, especially with the appearance in 1974 of his detective Pepe Carvalho as the protagonist of the crime novel series. It is essential to approach the author's poetry in order to understand the multiple facets of his writing. Therefore, this article proposes an approach to Montalban's poetry from some vital keys that transit in his work.
Keywords: poetry; culture of crossbreeding; sentimental journey; memory and desire; freedom; Manuel Vázquez Montalbán